PARTIAL LEAST SQUARES MODELLING OF FACTORS INFLUENCING EMPATHY AMONG MALAYSIAN SECONDARY SCHOOL STUDENTS - Rosnani Hashim; Abdulmajid Mohammed Aldaba; Mohamed Aslam M.Haneef; Mohamad Fauzan Noordin (Malaysian Journal of Learning and Instruction, 2023)
Purpose - The importance of the affective domain in holistic human development, in particular empathy, is an increasing concern today especially after the Covid-19 pandemic. The purpose of this study was threefold: (i) to investigate the attitudes of school students toward competencies associated with human consciousness; (ii) to validate the psychometric properties of the model of Malaysian school students’ empathy, and (iii) to examine the influence of school students’ selfefficacy, emotion regulation, sense of belonging and problem-solving on their empathy. Methodology - Using a quantitative survey approach, data were collected from 911 students drawn from 10 schools throughout Malaysia using a four-point Likert scale instrument. The study employed variance-based SEM by using Smart-PLS to achieve the objectives. First, the measurement model was employed to test the psychometric properties (such as convergent validity, divergent validity, and reliability) for all constructs. Second, the structural model was conducted to test the direct and indirect hypothesized relationship. Results - The measurement model provided evidence for the convergent and discriminant validity of the study constructs. The hypothesized structural model exhibited that three out of the four constructs, i.e., emotion regulation, sense of belonging and problem-solving have a direct influence on Malaysian school students’ empathy. Furthermore, emotion regulation showed a mediating role in the relationship between the exogenous variables (sense of belonging and problemsolving) and students’ empathy. The model explained 58.6 percent of the variance in the Malaysian school students’ empathy. Significance - This study is a pioneering work in Malaysia. With the identification of the factors that influence Malaysian school students’ empathy, i.e., students’ emotion regulation, sense of belonging and problem-solving, more effective support and interventions can be provided by teachers and the Ministry of Education to help in enhancing school students’ empathy.